PENDIDIKAN ISLAM DALAM BIMBINGAN DAN KONSELING ISLAM - Manja (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2020)
This study aims to examine Islamic education in Islamic guidance and counseling, as an attempt to describe and explain the problems of education in general and Islamic education, and the relationship between Islamic education in Islamic guidance and counseling. The development of today's era greatly affects the world of education, so that in the world of education there are many new discoveries that change the mindset of educators, from a conventional mindset to a modern mindset. Islamic education is a process of preparing the younger generation to fill roles, transferring knowledge and Islamic values ​​that are aligned with human functions to do good in the world and reap the rewards in the hereafter. Guidance and counseling is an integral part of education, meaning an inseparable part, a comprehensive part, a part that infiltrates all parts of education. Islamic education places humans as the main subject and target for developing all the potential that exists in order to become a more perfect human being (insan kamil) to get a share of the world and the hereafter.